When Autoimmunity ‘DRESSes up’: A Case after Certolizumab Therapy - Marigliano, Benedetta; Rosa, Federico; Internullo, Mattia; Scuro, Luigi; Tavanti, Andrea; Del Vecchio, Lucia Rita; Romagno, Francesco Paolo; Schito, Maria Barbara; Pace, Federica; Colombo, Giovanni Maria; Guglielmelli, Emanuele (European Journal of Case Reports in Internal Medicine, 2022)
Drug Reaction with Eosinophilia and Systemic Symptoms (DRESS) is characterised by skin rash together with visceral organ involvement, lymphadenopathy, eosinophilia and atypical lymphocytosis. The syndrome is clinically heterogeneous, making diagnosis challenging. It has an annual incidence of 2 per 100,000 population and a mortality rate of 2–10%. We describe the first case of DRESS induced by certolizumab, a biologic disease-modifying antirheumatic drug (bioDMARD).